Web-based geographic information system for the location of computer equipment service centers in the city of Medan - Rina Juwita Sari (Cebong Journal, 2022)
Medan City is one of the metropolitan cities in Indonesia with a population density in various fields and has various kinds of information related to its geographical location, such as road information and the location of a computer equipment service center, shopping places and so on. Of course, this information is needed by various parties for their respective needs. The absence of media for the community in finding a location makes it difficult for the community to find a place, especially the Computer Equipment Service Center. The community needs information about the geographical location of the computer equipment service center in Medan City digitally so that the community can more easily find the location and information about the computer equipment service center. With this problem, then giving the author an idea to raise the title "Geographical Information System Location of Web-Based Computer Equipment Service Centers in Medan City" in the preparation of this thesis. With this application, the author hopes to be able to help the community in finding the location of a computer equipment service center in the city of Medan. The programming language used to design this application is PHP, MySql as the database and ArcView as the map making application